2013
DOI: 10.1021/cs4001046
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Aluminum(salen) Catalyzed Synthesis of Oxazolidinones from Epoxides and Isocyanates

Abstract: The bimetallic aluminum(salen) complex [Al-(salen)] 2 O is shown to catalyze the synthesis of oxazolidinones from epoxides and isocyanates. The reaction is demonstrated to proceed with overall retention of epoxide stereochemistry, and both aromatic and aliphatic isocyanates can be used as substrates. In contrast to the corresponding reactions between epoxides and carbon dioxide or carbon disulfide which are also catalyzed by [Al(salen)] 2 O, no cocatalyst is needed in the reactions with isocyanates. A mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
74
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 79 publications
(151 reference statements)
4
74
0
Order By: Relevance
“…Subsequently, mononuclear aluminium(salen) complexes were shown to catalyse the reaction between epoxides and carbon disulfide under harsher reaction conditions 17. Complex 9 (in the absence of a cocatalyst) would also catalyse the synthesis of oxazolidinones 5 from epoxides and isocyanates18 (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, mononuclear aluminium(salen) complexes were shown to catalyse the reaction between epoxides and carbon disulfide under harsher reaction conditions 17. Complex 9 (in the absence of a cocatalyst) would also catalyse the synthesis of oxazolidinones 5 from epoxides and isocyanates18 (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Since these reactions occur with inversion of configuration at the carbon centre at the initial stage of the reaction (i.e., nucleophilic attack of the carbamate reagent onto the epoxide‐Al complex), those reactions that involve cis ‐configured carbon centres in the oxirane unit give rise to oxazolidinones with a trans disposition ( cf ., syntheses of 1–3 and 11a ). Thus these conversions proceed with formal inversion unlike the reactions between isocyanates and epoxides 29. This inversion pathway was further substantiated by the synthesis of 11b ( cis diastereoisomer of 11a ; dr >99%) that was prepared from the trans ‐epoxide.…”
Section: Resultsmentioning
confidence: 84%
“…Toluene was initially selected as a solvent for the reaction as it has previously been shown to be a suitable solvent for oxazolidinone synthesis ,. The use of toluene had a beneficial effect on the reaction, enabling quantitative conversion of styrene oxide into a 1:1.3 ratio of oxazolidinones 6 a and 7 a in 24 h when 5 mol % of both complex 10 and tetrabutylammonium bromide were used as the catalyst system (Table , entry 4).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that bimetallic aluminium(salen) complex 8 (Figure ) is an active catalyst for the reaction of epoxides with carbon dioxide, carbon disulfide, and isocyanates ,. For the synthesis of oxazolidinones, the optimal conditions were 5 mol % of catalyst at 80 °C for 24 h in a non‐polar solvent such as toluene.…”
Section: Introductionmentioning
confidence: 99%